Middle Islamic Jerash (9th Century-15th Century): Archaeology and History of an Ayyubid Mamluk settlement, by Achim Lichtenberger and Rubina Raja, (eds.) - Walker, Bethany J. (Journal of Islamic Archaeology, 2020)
Middle Islamic Jerash (9th Century-15th Century): Archaeology and History of an Ayyubid Mamluk settlement, by Achim Lichtenberger and Rubina Raja, (eds.). Jerash Papers 3, Turnhout: Brepols, 2018, 228 pp., €70. ISBN-13: 9782503578125.